Global response patterns of plant photosynthesis to nitrogen addition: A meta‐analysis. (8th April 2020) - Liang, Xingyun; Zhang, Tong; Lu, Xiankai; Ellsworth, David S.; BassiriRad, Hormoz; You, Chengming; Wang, Dong; He, Pengcheng; Deng, Qi; Liu, Hui; Mo, Jiangming; Ye, Qing
Abstract: A mechanistic understanding of plant photosynthetic response is needed to reliably predict changes in terrestrial carbon (C) gain under conditions of chronically elevated atmospheric nitrogen (N) deposition. Here, using 2, 683 observations from 240 journal articles, we conducted a global meta‐analysis to reveal effects of N addition on 14 photosynthesis‐related traits and affecting moderators. We found that across 320 terrestrial plant species, leaf N was enhanced comparably on mass basis ( N mass, +18.4%) and area basis ( N area, +14.3%), with no changes in specific leaf area or leaf mass per area. Total leaf area (TLA) was increased significantly, as indicated by the increases in total leaf biomass (+46.5%), leaf area per plant (+29.7%), and leaf area index (LAI, +24.4%). To a lesser extent than for TLA, N addition significantly enhanced leaf photosynthetic rate per area ( A area, +12.6%), stomatal conductance ( g s, +7.5%), and transpiration rate ( E, +10.5%). The responses of A area were positively related with that of g s, with no changes in instantaneous water‐use efficiency and only slight increases in long‐term water‐use efficiency (+2.5%) inferred from 13 C composition. The responses of traits depended on biological, experimental, and environmental moderators. As experimental duration and N load increased, the responses of LAI and A area diminished while that of E increased significantly. The observed patterns of increases in both TLA and E indicate that N deposition will increase the amount of water used by plants. Taken together, N deposition will enhance gross photosynthetic C gain of the terrestrial plants while increasing their water loss to the atmosphere, but the effects on C gain might diminish over time and that on plant water use would be amplified if N deposition persists. Abstract : Atmospheric nitrogen deposition continues to be a major component of global change to impact plant functioning. Here, using 2, 683 observations from 240 journal articles, we showed that across the globe, nitrogen addition significantly enhanced total leaf area and, to a lesser extent, leaf photosynthetic capacity, indicating that nitrogen deposition may facilitate gross photosynthetic carbon gain of the terrestrial plants. However, the effects of nitrogen addition on plant photosynthesis might diminish over time and that on plant transpiration would be amplified if nitrogen deposition persists.